Wastewater irrigation and health: challenges and outlook for mitigating risks in low-income countries - Scott, Christopher A.; Drechsel, Pay; Raschid-Sally, Liqa; Bahri, Akissa; Mara, D.; Redwood, M.; Jiménez, B. (2010)
Wastewater irrigation is a widespread and growing phenomenon that carries varying degrees of risk. Whether spontaneously practiced in urban and periurban agriculture or planned as part of water reuse programmes, food and fodder production using untreated sewage or treated effluent can have serious human health implications for farmers and consumers, and can irreversibly degrade the environment. In low-income countries water pollution is often the result of inadequate wastewater collection and treatment, and unplanned release to receiving water bodies. Making wastewater irrigation safer depends on a location-specific combination of different pathogen barriers including, where possible, appropriate wastewater treatment. Ensuring that these strategies work in an integrated, mutually supportive manner requires a multi-sectoral paradigm shift in the common approach of wastewater management for disposal. Additionally, it is crucial to continue research (especially in developing countries) on the types and severity of risk, locally feasible mitigation options, the cost-effectiveness of safer wastewater irrigation practices compared to other interventions against diarrhoea and facilitating the adoption of ?non-? or ?post-treatment? options. This concluding chapter presents an outlook for wastewater irrigation by integrating the major findings of the present volume, synthesizing key elements of the current global status and challenges of sanitation and wastewater irrigation with emphasis on the WHO Guidelines. It also highlights wastewater-governance opportunities with the greatest potential to support safe wastewater irrigation that simultaneously address the combined challenges deriving from the global sanitation, water and food crises.